Bibliometric Analysis to Understand Research Trends in Data-Driven Economics - Judijanto, Loso; Muni, Komang Shanty; Amir, Firlie Lanovia (Westscience Press, 2024)
The bibliometric analysis conducted in this study offers a nuanced understanding of the evolution and current state of research within data-driven domains, highlighting